2020
DOI: 10.3389/fimmu.2020.00392
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Adipose Tissue-Derived Human Antibodies With “Anti-self” Specificity

Abstract: We have previously shown that the human obese adipose tissue (AT) contributes to increased secretion of adipocyte-specific IgG antibodies in individuals with obesity. This occurs without any exogenous stimulation, because the ongoing process of cell death in the obese AT leads to the release of "self" antigens able to induce chronic stimulation of B cells. We have identified several mechanisms responsible for the release of "self" antigens, such as hypoxia, cell cytotoxicity, and DNA damage. In this paper, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 26 publications
3
29
0
Order By: Relevance
“…These results altogether suggest that obesity induces B cells characterized by a higher metabolic profile which is needed to support their increased IA and function, including the production of pro-inflammatory mediators that support local and systemic inflammation. The higher metabolic phenotype of B cells from the AT is also associated with increased secretion of IgG antibodies with autoimmune specificity, as we have previously shown [29,30].…”
Section: B Cells From the At Of Individuals With Obesity Are Highly Mmentioning
confidence: 51%
See 1 more Smart Citation
“…These results altogether suggest that obesity induces B cells characterized by a higher metabolic profile which is needed to support their increased IA and function, including the production of pro-inflammatory mediators that support local and systemic inflammation. The higher metabolic phenotype of B cells from the AT is also associated with increased secretion of IgG antibodies with autoimmune specificity, as we have previously shown [29,30].…”
Section: B Cells From the At Of Individuals With Obesity Are Highly Mmentioning
confidence: 51%
“…B cells are among the first immune cell types that infiltrate the obese AT in both mice [ 41 , 42 , 43 ] and humans [ 30 ], where they secrete pro-inflammatory mediators, regulate inflammatory T cells and macrophages, and secrete pathogenic IgG antibodies with autoimmune specificities [ 29 , 43 ]. Therefore, depletion of systemic [ 43 ] or AT-derived [ 41 ] B cells, through intra-peritoneal or intra-AT injection with an anti-CD20 depleting monoclonal antibody, has shown to significantly improve metabolic and immunological function of the tissue in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies with human B cells have shown that higher intrinsic inflammation in unstimulated B cells from elderly individuals, as compared to B cells from young individuals, is positively associated with the secretion of IgG antibodies with autoimmune specificity [ 16 ]. This occurs because B cells from elderly individuals are already pre-activated, a status leading to spontaneous secretion of autoimmune antibodies, also observed in autoimmune diseases [ 17 ], and in the obese adipose tissue [ 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this paper we evaluated the metabolic profile of B cells isolated from the spleens of young and old mice, with the aim to identify metabolic pathways associated with intrinsic B cell inflammation and with the secretion of autoimmune antibodies. We focused on the secretion of autoimmune antibodies because our recent human B cell results [ 16 ] have shown that higher intrinsic inflammation in unstimulated B cells from elderly individuals induces a “pre-activation” status associated with the secretion of IgG antibodies with autoimmune specificities, similar to what has been observed in autoimmune diseases [ 17 ], and in the obese adipose tissue at least for some specificities [ 18 , 19 ]. In order to identify the B cell subset(s) driving the phenotype and function of B cells in the splenic B cell pool of old mice, we sorted the major splenic B cell subsets, Follicular (FO) and Age-associated B cells (ABCs).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we have shown that the human obese AT contributes to increased secretion of adipocyte-specific IgG antibodies and this occurs without any stimulation, likely because the ongoing process of cell death in the obese AT leads to the release of “self” antigens, that are almost exclusively intracellular or cell-associated, able to chronically stimulate B cells ( 28 ). Adipocyte-specific IgGs secreted in the obese AT are significantly correlated with those present in the plasma ( 79 ).…”
Section: Effects Of Obesity On Human B Cellsmentioning
confidence: 99%